2022
DOI: 10.3390/biology11070990
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Stress Effect on the Red Cusk-Eel (Geypterus chilensis) Liver: Transcriptional Modulation and Oxidative Stress Damage

Abstract: Environmental stressors, such as temperature, are relevant factors that could generate a negative effect on several tissues in fish. A key fish species for Chilean aquaculture diversification is the red cusk-eel (Genypterus chilensis), a native fish for which knowledge on environmental stressors effects is limited. This study evaluated the effects of high-temperature stress on the liver of red cusk-eel in control (14 °C) and high-temperature (19 °C) groups using multiple approaches: determination of plasmatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…As the most vital organ in M. albus , the liver is directly communicates with the heart, intestine and gallbladder, related to growth and development, substance metabolism, detoxification, and hematopoiesis and can also reflect the physiological, pathological, and nutritional status of M. albus . Excessive temperature can also cause structural damage to fish, especially the liver, which has been confirmed in many species ( Dettleff et al, 2022 ; E. Liu et al, 2022 ; Zhao et al, 2022 ). Excessive temperature will also stimulate the production of endogenous reactive oxygen species (ROS) ( Wiens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…As the most vital organ in M. albus , the liver is directly communicates with the heart, intestine and gallbladder, related to growth and development, substance metabolism, detoxification, and hematopoiesis and can also reflect the physiological, pathological, and nutritional status of M. albus . Excessive temperature can also cause structural damage to fish, especially the liver, which has been confirmed in many species ( Dettleff et al, 2022 ; E. Liu et al, 2022 ; Zhao et al, 2022 ). Excessive temperature will also stimulate the production of endogenous reactive oxygen species (ROS) ( Wiens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…Autophagy is triggered by various stimuli, including lack of nutrients, reactive oxygen species (ROS), endoplasmic reticulum stress, and the presence of microorganisms [35]. Although various reports in teleosts have investigated autophagy in processes such as reproduction [36][37][38], hepatic metabolism [13,39,40], and immune response to infections [41,42], there is limited evidence of the role of autophagy in skeletal muscle catabolism. Studies of fine flounder (Paralichthys adspersus) have shown that stress induced by high-density farming can upregulate the expression of genes involved in the autophagy process, which is believed to be protective mechanism against apoptosis regulated by the ubiquitin-proteasome pathway [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted on a marine teleost species, red cusk-eel (Genypterus chilensis), it was found that thermal stress leads to skeletal muscle oxidation and atrophy [12]. Additionally, RNA-Seq assays revealed that high-temperature stress induced the expression of various autophagyassociated genes in the liver of the species [13]. Autophagy is a fundamental cellular mechanism that plays an essential role in energetic catabolism and the lysosome-mediated degradation of cell components.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of different stressors was analyzed in different works included in this Special Issue. Dettleff et al [ 11 ] evaluated the effects of high-temperature stress on the liver of red cusk-eel ( Genypterus chilensis ) through different approaches, including RNA-Seq analysis. The results revealed that this stressor induced oxidative damage in the liver and affected the expression of a multitude of genes, which are mainly involved in the unfolded protein response, heat shock response, and oxidative stress, among others, providing a rich source of information to be considered for the aquaculture and fisheries industry of this species under a climate change scenario [ 11 ].…”
mentioning
confidence: 99%
“…Dettleff et al [ 11 ] evaluated the effects of high-temperature stress on the liver of red cusk-eel ( Genypterus chilensis ) through different approaches, including RNA-Seq analysis. The results revealed that this stressor induced oxidative damage in the liver and affected the expression of a multitude of genes, which are mainly involved in the unfolded protein response, heat shock response, and oxidative stress, among others, providing a rich source of information to be considered for the aquaculture and fisheries industry of this species under a climate change scenario [ 11 ]. Interestingly, Naya-Catalá et al [ 12 ] found that gilthead sea bream ( Sparus aurata ) juveniles acclimated for 45 days to mild-hypoxia and then returned to normoxia showed an increased contribution of lipid metabolism to the whole energy supply to preserve the aerobic energy production, a better swimming performance regardless of changes in feed intake, as well as reduced protein turnover and improved anaerobic fitness with the restoration of normoxia.…”
mentioning
confidence: 99%